Clinical Evaluation of Jalaukavacharana (Medicinal Leech Therapy) in Non-Healing Ulcer - Gaurav Parmar; Nidhi Sharma (AYUSHDHARA, 2023)
Chronic non-healing ulcers are those that do not heal within three months or often remain in the inflammatory stage for too long and may never heal or may take years. Some wounds heal easily by body’s self-healing mechanism and some poses challenge to normal wound healing and does not heal in time and becomes a matter of concern for the physicians. Leech therapy proved to be a better treatment option by benefits of its salivary constituents in wound healing. It is an ancient way of treating such complicated disorders mentioned in different texts. A patient came at Shalya Tantra OPD with ulcer on posterior aspect of right ankle joint above the heel which was not healing since 6 months even on daily antiseptic dressings. Patient gave h/o immobilization for 2 months following ORIF of same joint 7 months back. During immobilization, after 1month of ORIF, patient developed ulcer at posterior aspect of Rt. Ankle above heel. Leech was applied at wound site twice weekly initially followed by once weekly then once in 15 days along with antiseptic dressing daily. The ulcer started showing signs of healing within three sittings and completely healed by 4 months. This study was carried out in Department of Shalya Tantra, Rajiv Gandhi govt. Post Graduate Ayurvedic college and Hospital, Paprola.